Measuring empowerment in the abaca, coconut, seaweed and swine value chains in the Philippines - Malapit, Hazel J. (International Food Policy Research Institute, 2018)
Presented by Hazel Malapit (IFPRI/A4NH), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.